Analisis Karya Wassily Kandinsky Mengenai Melodi Dan Warna Dalam Pembuatan Karya Seni - Fatimah Azzahra; Yayan Suherlan (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Synesthesia is a phenomenon where the human senses can receive data and turn it into a stimulation to certain sensory, but indirectly the stimulation can trigger other stimulation. Chromesthesia is one of the branches of Synesthesia, Chromesthesia is a phenomenon where humans can associate colors to a sound that is heard, Wassily Kandinsky is one of the humans blessed with this advantage. This research aims to dissect Wassily Kandinsky's work on melody and color. As one of the humans blessed with Chromesthesia, whether his works are strongly influenced by this advantage. Using a qualitative approach with a descriptive method. Data will be presented taken from observations of Wassily Kandinsky's works. It was found that some of Wassily Kandinsky's works entitled Composition VIII were created after he watched Wagner's opera “Lohengrin” performed at the Bolshoi Theater in 1896. His works were based on the melodies he heard while watching the opera, Wassily Kandinsky felt the colors as he listened to the music presented in the opera.